Penatalaksanaan Fisioterapi pada Post ORIF Fraktur Radius 1/3 Proximal Sinistra dengan Infra Red dan Terapi Latihan - Fadel Ahmad Dzaky; Zainal Abidin (Lembaga Pengembangan Kinerja Dosen, 2026)
A fracture is a condition in which there is a partial or complete loss of bone or cartilage continuity caused by direct or indirect trauma. In the case of a fracture of the proximal one-third of the left radius, the injury generally occurs due to a strong impact or direct trauma to the left arm, often resulting from a traffic accident or a fall. Patients with this condition typically experience several problems, including pain at the fracture site, decreased muscle strength, limited range of motion (ROM), and functional activity disturbances such as difficulty in gripping, lifting, or writing. Physiotherapy management plays a crucial role in restoring upper limb function. The methods used include Infrared (IR) therapy and Exercise Therapy (ET). Infrared therapy helps improve blood circulation, reduce muscle spasms, and alleviate pain through the application of heat. Meanwhile, Exercise Therapy consists of Free Active Exercise, Passive Exercise, and Resisted Active Exercise, which aim to increase muscle strength, improve joint mobility, and gradually restore the patient’s functional abilities. The results of the physiotherapy intervention showed a significant reduction in pain, increased muscle strength, improved ROM, and enhanced functional activity of the left upper extremity, allowing the patient to return to daily activities more optimally and independently.